Reconstructing the Hijab-Mahjub Concept in Islamic Inheritance Law: A Critical Analysis of Islamic Inheritance Law and KHI - Defel Fakhyadi (Jurnal Hukum Keluarga, 2025)
Hijab is a form of inheritance obstruction in Islam that occurs when there are heirs who are given higher priority. The position of these prioritized heirs determines the inheritance rights of others and categorizes them as the first-rank heirs. Although the rules of hijab are essentially egalitarian for both men and women, cultural influences and the interpretive tendencies of scholars in understanding the Qur’anic verses on inheritance often produce patriarchal interpretations. In fact, the Qur’an fundamentally grants equal status to men and women as heirs. This literature-based study aims to reveal various forms of injustice within the concept of hijab in Islamic inheritance law. The research employs a qualitative descriptive method grounded in library research, with data analyzed through a critical-descriptive approach. This method produces a more comprehensive understanding of the rules of hijab within the Islamic inheritance system. The study concludes that the commonly accepted concept of hijab–mahjub contains misogynistic bias against women. Such discriminatory tendencies result in women being viewed as having lower status than men, even though both hold equal positions as heirs—despite receiving different shares. Therefore, a universal and comprehensive legal understanding is needed to prevent discrimination against women in the application of Islamic inheritance law. The interpretations of classical scholars, which were influenced by the sociological conditions of patrilineal Arab society, must be reconstructed to promote reforms in Islamic law that are more relevant, dynamic, and aligned with contemporary developments as well as the foundational principles of Islamic inheritance law.